Potential for Legalization of Marijuana According to Islamic Law in The Study of The Rules of Fathu Dzariah wa Saddu Dzariah - Ade Nur Rizal Lul Huda; M. Junaidi; Indah Maulani (Universitas Muhammadiyah Surakarta, 2023)
Determining the illegalization of marijuana in Indonesia always reaps many pros and cons in society. Law Number 35 of 2009 concerning Narcotics is the main basis for prohibiting marijuana plants for medical purposes, even though some treatments require the Thetrahydrocannabinol or THC-9 content of marijuana plants. Various attempts to release marijuana from Category I narcotics have occurred many times, both through literature from the marijuana research community, and even PUU before the Constitutional Court. The Ministry of Health has repeatedly issued regulations regarding the classification of Narcotics, but Marijuana is still in Class I Narcotics. In Islamic law, Marijuana is legal in jurisprudence in qiyas by several fiqh scholars with Khamr because it has similarities in the consequences of its use, namely loss of mind, even though The origin and substances contained are different. But there are several scholars who do not agree with this qiyas, this is based on Khamr which has no benefits at all while Ganja still has benefits in it, moreover, no Nash clearly mentions the prohibition of Marijuana in Islam. This research was conducted using the Normative Juridical research method, so this research will focus on the legislative approach, conceptual approach, approach to Islamic law and analysis of the rules of Usul Fiqh. The final aim is to state whether marijuana is worthy of being legalized in Indonesia in the study of the fiqh proposals of Fathu Dzariah and Saddu Dzariah's rules.